Impacts of Nitrogen Deficiency on Wheat (Triticum aestivum L.) Grain During the Medium Filling Stage: Transcriptomic and Metabolomic Comparisons - Wang, Yanjie; Wang, Demei; Tao, Zhiqiang; Yang, Yushuang; Gao, Zhenxian; Zhao, Guangcai; Chang, Xuhong (Frontiers in Plant Science, 2021)
Nitrogen (N) supplementation is essential to the yield and quality of bread wheat (Triticum aestivum L.). The impact of N-deficiency on wheat at the seedling stage has been previously reported, but the impact of distinct N regimes applied at the seedling stage with continuous application on filling and maturing wheat grains is lesser-known, despite the filling stage being critical for final grain yield and flour quality. Here we compared the phenotype characteristics including grain yield, grain protein and sugar quality, plant growth, leaf photosynthesis of wheat under N-deficient and N-sufficient conditions imposed prior to sowing (120 kg/hm2) and in the jointing stage (120 kg/hm2), and then evaluated the effects of this continued stress through RNA-seq and GC-MS metabolomic profiling of grain at the mid-filling stage. The results showed that except for an increase in grain size and weight, the content of total sugar, starch and fiber in bran fraction and white flour, the other metrics were all decreased under N-deficiency. A total of 761 differentially expressed genes (DEGs) and 77 differentially accumulated metabolites (DAMs) were identified. Under N-deficiency, 51 down-regulated DEGs were involved in the reduction of chlorophyll synthesis, chloroplast development, light harvesting, and electron transfer functions of photosystem, consisted with the SPAD and Pn value decreased by 32% and 15.2%, impeded photosynthesis. 24 DEGs implicated the inhibition of amino acids synthesis and protein transport, in agreement with 17-42% reduction of ornithine, cysteine, aspartate and tyrosine from metabolome, and a 18.6% reduction in grain protein content. However, 14 DEGs were implicated in promoting sugar accumulation in the cell wall and another 6 DEGs also enhanced cell wall synthesis, which significantly increased fiber content in the endosperm and likely contributed to increasing the thousands-grain weight (TGW). Moreover, RNA-seq data suggested that wheat also improved its capacity for DNA repair, iron uptake, disease and abiotic stress resistance, oxidative stress scavenging and increased anthocyanidin, flavonoid, GABA, galactose, and glucose levels under N-deficiency. Our study identified candidate genes and metabolites related to low-N adaption and tolerance that may provide new insights into a comprehensive understanding of the genotype-specific differences in performance under N-deficiency.